2017
DOI: 10.1097/aco.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cost of acute and chronic kidney disease after cardiac surgery

Abstract: Purpose Acute and chronic kidney diseases (AKI and CKD) have far-reaching implications for surgical patients in regards to postoperative outcomes and hospital cost. We review the recent literature on the effects of AKI and CKD on morbidity, mortality, and resource utilization among cardiac surgery patients. Recent findings Both AKI and CKD increase the risk for short and long-term mortality, morbidity, length of stay, and hospital cost among postoperative patients, with increasing disease stage correlating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…The permanency of patient in the hospital was minimally estimated in 15 days, in contrast, the maximum was 82 days. Acute kidney injury is a problem to health resulting from different causes and is related to high mortality rates and long periods of hospital admission (8) , finding identified in the present study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The permanency of patient in the hospital was minimally estimated in 15 days, in contrast, the maximum was 82 days. Acute kidney injury is a problem to health resulting from different causes and is related to high mortality rates and long periods of hospital admission (8) , finding identified in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…The acquisition of better comprehension about survivors´ clinical history with hospital renal injury, at greater risk for progressive chronic kidney disease and death is vital importance for public health. Scientific evidences have showed that milder forms of renal injury, that not require dialysis are associated to short and long-term mortality (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…Our study reports increase resource utilization in terms of increase LOS and cost of hospitalization in patients with ESRD undergoing TMVr. The results have been replicated in studies looking at renal disease cost in patients with coronary artery and valvular disease 31,32 …”
Section: Discussionmentioning
confidence: 86%
“…It is associated with an increase in mortality, short- and long-term morbidity, chronic kidney disease, and cardiovascular disease [37]. An episode of postoperative AKI imposes an average hospital cost increase of $9000, even after adjusting for all other complications [8, 9]. The implementation of existing clinical guidelines for prevention and treatment of AKI is often hindered by the inability to accurately and timely assess the risk for AKI while accounting for the dynamic nature of the pathophysiological events during surgery.…”
Section: Introductionmentioning
confidence: 99%